Suivre la piste du CO2 pour rencontrer spiritus sylvestris - Anne-Sophie Milon (Ateliers d'Anthropologie)
This science fiction attempts to take a different view of the icon of climate change: the carbon dioxide (CO2) within the Keeling Curve. It begins by recounting the geochemical experiment by Charles D. Keeling (1928-2005), linking it with the findings of research by two predecessors: Svante A. Arrhenius (1859-1927) and Guy S. Callendar (1898-1964). Then it wonders what process could have activated these scientists’ change of state—from enthusiasm to fear—in the face of rising atmospheric CO2 during the 20th century. Then it contextualises their findings through a geological history of the understanding of Earth in the 19th and 20th centuries. Thus it can take a different view of the chemical history of CO2 and reinterpret the Keeling Curve as Keeling’s summoning of a new being with new skills within his observatory-laboratories: spiritus sylvestris.